2014
DOI: 10.1021/es500906d
|View full text |Cite
|
Sign up to set email alerts
|

Redox Properties of Plant Biomass-Derived Black Carbon (Biochar)

Abstract: Soils and sediments worldwide contain appreciable amounts of thermally altered organic matter (chars). Chars contain electroactive quinoid functional groups and polycondensed aromatic sheets that were recently shown to be of biogeochemical and envirotechnical relevance. However, so far no systematic investigation of the redox properties of chars formed under different pyrolysis conditions has been performed. Here, using mediated electrochemical analysis, we show that chars made from different feedstock and ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
522
5
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 886 publications
(554 citation statements)
references
References 95 publications
25
522
5
2
Order By: Relevance
“…This functionality is similar to those of activated carbon and solid humic substances reported in previous studies (Roden et al 2010;Van Der Zee et al 2003). Electrochemical measurements showed that all of the tested biochars had modest EACs, and the EAC of R900 was comparable with that of biochars and activated carbon (AC) in previous studies (Kluepfel et al 2014;Van Der Zee et al 2003), where AC was verified to accept microbial extracellular electron at a capacity of approximately 315 mmol e ¡ /g. The present results for the growth of G. sulfurreducens provide a potential explanation for the observations that biochar amendments in the paddy soil increased the relative abundance of Fe(III)-reducing bacteria or quinone-respiring biomass (Tong et al 2014).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This functionality is similar to those of activated carbon and solid humic substances reported in previous studies (Roden et al 2010;Van Der Zee et al 2003). Electrochemical measurements showed that all of the tested biochars had modest EACs, and the EAC of R900 was comparable with that of biochars and activated carbon (AC) in previous studies (Kluepfel et al 2014;Van Der Zee et al 2003), where AC was verified to accept microbial extracellular electron at a capacity of approximately 315 mmol e ¡ /g. The present results for the growth of G. sulfurreducens provide a potential explanation for the observations that biochar amendments in the paddy soil increased the relative abundance of Fe(III)-reducing bacteria or quinone-respiring biomass (Tong et al 2014).…”
Section: Discussionsupporting
confidence: 87%
“…It should be noted that quinone moieties, phenolic moieties and condensed aromatics in biochar are the possible redox-active moieties responsible for its EAC (Kluepfel et al 2014). These functional groups vary with pyrolysis conditions, heat-treatment temperatures, residence time, and feedstock; thus, EAC values can vary significantly among different biochars, leading to their varied functionalities in microbial respiration and cell yield.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore conclude that the influence of local pH alteration in the root zone cannot, or only to a minor extent, explain the strong differences in yield. Further biochar effects in the root zone potentially amplified by the concentrated deposit application might be expected for redox potential [71,72], CEC [73,74] and microbial activity [75] although this is outside the scope of this study and clearly needs more research.…”
Section: Resultsmentioning
confidence: 96%
“…Like HULIS or humic substances, the different kinds of black carbons act as redox mediators due to their oxygen functionalities bound to the aromatic hexagon network such as hydroxyl, carbonyl and ether (Klüpfel et al, 2014;Oh and Chiu, 2009). These functionalities similarly act as hydroquinone, quinone, aromatic ether, pyrylium and pyrone in the extended graphene planes as electron acceptors and donor moieties.…”
Section: Oxidation Of Organic Aerosol Particles Containing Black and mentioning
confidence: 99%